Protex 51FP as a starter for accelerating fish sauce fermentation from anchovy (Stolephorus commersonii) - Chau, Le Minh; Ngoc, Ho Thi Bich; Moreno, Claire Donnay; Bruzac, Sandrine; Bergé, Jean-Pascal; Bergé, Jean-Pascal; Hanh, Vu Thi (Emirates Journal of Food and Agriculture, 2021)
In this 180-day study, commercial Protex 51FP enzyme effects as a starter culture on anchovy fish sauce fermentation were investigated. Three fish source fermentation groups, including a control group (the anchovy with 25% of salt addition), E group (the anchovy with 25% of salt and 1% of Protex 51FP addition), and E (-s) group (the anchovy with 1% of Protex 51FP and after 6 hours with 25% of salt), were compared. The fish sauce fermentation groups were sampled, packed into glass jars (10 liters), and covered by a lid at ambient temperature (22 - 30°C) for 180 days. Three commercial fish sauces were also included as nutritional references. The results showed that the addition of Protex 51FP achieved positive results of total nitrogen content and amino acids compared to the control samples (p<0.05). These values were competitive with commercial product figures. Total amino acids in 8000mg/100ml fish sauce were significantly higher than those in the control. There were rich in essential amino acids (41-43%) and small peptides (13% peptides with a molecular weight below 200 Da, 32-39% peptides with a molecular weight below 130 - 200 Da, and 25-28% of peptides with a molecular weight below 200 – 360 Da). Compared with traditional methods, the addition of Protex 51FP (p<0.05) could improve the quality of fish sauce and obtain greater nutritional values. In all experiments, the color of adding-enzyme samples was darker than that of the traditional products, and the smell of these samples (including traditional methods) was not as quite strong as commercial products.